Manufacture and Characterization of Adsorbers Utilizing Pahae Natural Zeolite-Chicken Eggshell for Purifying Used Cooking Oil - Susilawati, Susilawati; Alfira, Bella (Talenta Publisher, 2023)
This research investigates the synthesis and characterization of Pahae natural zeolite-chicken eggshell adsorber to refine used cooking oil. The primary objective is to develop effective adsorbents for enhancing the quality of used cooking oil through refining. The methodology involves sieving the zeolite through a 74 µm sieve, chemically activating it using a 10% KOH solution for 1 hour and drying it at 100°C. The eggshells are also sieved through a 74 µm sieve, followed by washing and drying at 105°C for 12 hours. Various combinations of natural zeolite and chicken eggshell compositions (100% : 0%, 0%: 100%, 95%: 5%, 90%: 10%, 85%: 15%, 80%: 20%) are then prepared and pressed using a hydraulic press under a load mass of 6 tons for 10 minutes. The resultant samples are further activated by heat treatment at 600°C for 2 hours. The adsorbents undergo a comprehensive characterization process, encompassing physical properties (porosity and water absorption), mechanical properties (hardness), surface morphology (SEM), elemental composition (XRF), X-ray diffraction (XRD) analysis, and practical applications assessment (density, viscosity, moisture content, color, and odor). The optimal adsorbent configuration is identified as 80% natural zeolite and 20% chicken eggshell composition, activated at 600°C, exhibiting a porosity of 81.54% and an oil absorption of 46.86%. The highest hardness value of 119.64 MPa is achieved with 100% natural zeolite composition at 600°C. SEM analysis indicates an average pore diameter of 1.232 µm, while XRF results highlight calcium (Ca) as the predominant element at 49.64%. XRD analysis confirms the formation of a rhombohedral crystal structure.